Creativity among Prospective Early Childhood Teachers: The Effects of Screencast-O-Matic-Assisted Project-Based Learning - Jelita Jelita; Fenny Anggreni (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study investigated the effect of Screencast-O-Matic–assisted Project-Based Learning (PjBL) on the creativity of prospective Islamic early childhood education teachers in higher education. A quantitative method with a descriptive-associative design was employed. The participants were 75 sixth-semester students from the Islamic Early Childhood Education program at IAIN Langsa, Aceh, selected using the Slovin sampling technique. Data were collected using an observation checklist measuring four dimensions of creativity - fluency, flexibility, originality, and elaboration - and a questionnaire capturing students' responses toward the implementation of Screencast-O-Matic–assisted PjBL. Data analysis was conducted using Pearson's product–moment correlation, t-tests, and simple linear regression in SPSS version 20. The findings revealed that PjBL supported by Screencast-O-Matic had a positive and statistically significant effect on students' creativity (t = 2.312, p = 0.004). However, the strength of this relationship was relatively weak (r = 0.370), indicating that the learning model contributed only marginally to overall creativity development. Further analysis showed that the contribution of technology-assisted PjBL was not evenly distributed across creativity dimensions. The learning model was more effective in enhancing students' elaboration skills, particularly in organizing, developing, and presenting ideas in a structured manner, while its effect on originality remained limited. These results suggest that Screencast-O-Matic–assisted PjBL supports structured idea development rather than the generation of genuinely novel ideas, especially when instructional design does not explicitly target divergent thinking and originality. Consequently, although the learning model demonstrates a statistically significant contribution to creativity, the research objectives were only partially achieved. Future research is therefore recommended to employ mixed-method or experimental designs, develop project tasks that explicitly target originality and divergent thinking, and examine the long-term effects of technology-assisted PjBL on broader pedagogical competencies and professional readiness across diverse educational contexts.